Impact of platinum group elements on the soil invertebrate Folsomia candida - Nemcova, Barbora; Mikulaskova, Hana; Bednarova, Ivana; Beklova, Miroslava; Pikula, Jiri (Neuro endocrinology letters, 2013)
OBJECTIVES: Trace concentrations of the platinum group elements (PGE; Pt, Pd and Rh) are nowadays an irreplaceable part of environmental analysis and assessment. These rare elements are used as effective substances in automotive catalysts to reduce pollution by emissions originating from fuel combustion. Due to their harmful potential, it is necessary to monitor their content and behaviour in different samples. Effect assessment using ecotoxicological bioassays with organisms at different trophic levels can provide valuable pieces of information on the risk of chemical substances in the ecosystem. DESIGN: The experiments were carried out as described in the OECD Guideline 232 [CSN ISO 11267 - Soil quality - Inhibition of reproduction of Collembola (Folsomia candida) by soil pollutants]. The reproductive effects of palladium (PdCl2) and rhodium (RhCl3) were examined. Concentrations of PGE tested were as follows: 5, 10, 25, 50 and 100 µmol.L-1. The EC50 (medium effective concentration) was determined after 28 days of exposure. Inhibition of reproduction of PGE-exposed collembolans was compared against controls. RESULTS: Values of 28dEC50 of PdCl2 and RhCl3 amounted to 21.0 µmol.L-1 and 266.22 µmol.L-1, respectively. We can confirm that the relative order of toxicities is Pd (II) > Pt(IV) >> Rh(III). CONCLUSION: To the best of our knowledge, this is the first study to use Folsomia candida as an indicator species to assess the risk of soil contamination by palladium and rhodium. However, more toxicity data for various species are needed to evaluate the environmental risks of PGEs in soils.
Keywords: rhodium; Reproduction; Animals; Platinum; platina; rozmnožování; palladium; látky znečišťující půdu; Arthropods; členovci; zvířata; Rhodium; půda; Soil; Palladium; Soil Pollutants; Environmental Monitoring; monitorování životního prostředí